Memaknai Sawen Dalam Kehidupan Sosial Masyarakat Bali - I Wayan Wastawa (Kamaya: Jurnal Ilmu Agama, 2018)
The article aims to provide knowledge and understanding of Balinese cultural symbols. Bali as a tourist destination of the world has undergone many changes and problems, both social problems, law, criminalism, until the issue of solving the sacred religious symbols. One form of symbol to deliver understanding of symbols that are sacral and profane one of them is sawen. Sawen in Balinese life is a symbol that can also be significant intermediaries in the logical aspect (denotative) and significant in the psychological aspect (connotative), so sawen is a symbol that can give a message that must be understood by the community which use sawen as symbol. Similarly sawen will be meaningfull if the use of it is in accordance with space, time, shape and type of sawen, which will be accepted as the same message as well and is agreed with the ideas of its users. The use of sawen by the people of Bali, especially the Hindus can be used in sacred activities, sawen can also be used in the profane situation. Sawen can be regarded as a symbol of communication functions, as sawen can be used a tool for social interaction. An interaction through sawen occured, because of a comprehension and understanding of the use of the same sawen according to time and space usage. Thus sawen can have various meanings, such as: Sawen means ownership, Sawen means a bond, Sawen means prohibition messages, Sawen also means repellent reinforcements and a sign of religious ceremonies.